Evaluating the Role of Seagrass in Cenozoic CO2 Variations - Brandano, Marco; Cuffaro, Marco; Gaglianone, Giovanni; Petricca, Patrizio; Stagno, Vincenzo; Mateu-Vicens, Guillem (Frontiers in Environmental Science, 2016)
Marine seagrass angiosperms play an important role in carbon sequestration, removing carbon dioxide from the atmosphere and binding it as organic matter. Carbon is stored in the plants themselves, but also in the sediments both in inorganic and organic forms. The inorganic component is represented by carbonates produced by calcareous organisms living as epiphytes on seagrass leaves and rhizomes. In this paper, we find that the rate of seagrass epiphyte production (leaves and rhizomes), averages 400 g m-2 yr-1, as result of seagrass sampling at seven localities along the Mediterranean coasts, and related laboratory analysis. Seagrasses have appeared in the Late Cretaceous, becoming a place of remarkable carbonate production and C sequestration during the whole Cenozoic era. Here, we explore the potential contribution of seagrass as C sink on the atmospheric CO2 decrease by measuring changes in seagrass extent, which is directly associated with variations in the global coastal length associated with plate tectonics. We claim that global seagrass distribution significantly affected the atmospheric composition, particularly at the Eocene-Oligocene boundary, when the CO2 concentration fell to 400 ppm, i.e. the approximate value of current atmospheric CO2.